Positive electrode material for lithium battery, preparation method thereof, lithium battery and electrical device

CN123002907APending Publication Date: 2026-10-30CNGR ADVANCED MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510578660.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,相关技术中,一般需要1-2天的离子交换才能制备出纯度较高的O2相的钴酸锂,且制得的钴酸锂正极材料的压实密度和电化学性能较低

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002907A_ABST
    Figure CN123002907A_ABST
Patent Text Reader

Abstract

The application discloses a positive electrode material for a lithium battery, a preparation method of the positive electrode material, a lithium battery and an electrical device, and relates to the technical field of lithium batteries. c (Co y M 1‑y )O2 and a first soluble lithium salt in a first solvent to obtain a first intermediate product, wherein the first ion exchange is performed for a time T1 satisfying the relationship: 0.5h≤T1≤5h; and performing a second ion exchange on the first intermediate product and a second soluble lithium salt in a second solvent to obtain a second intermediate product, wherein the second ion exchange is performed for a time T2 satisfying the relationship: 0.5h≤T2≤5h, and the positive electrode material is prepared from the second intermediate product and has a chemical formula of Li a Na b (Co x M 1‑x )O2. The method shortens the total ion exchange time, and improves the compaction density and electrochemical performance of the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery technology, specifically relating to a positive electrode material for lithium batteries and its preparation method, lithium batteries, and electrical devices. Background Technology

[0002] Cathode materials are crucial components in lithium-ion batteries, playing a vital role in their performance. Lithium cobalt oxide, with its high specific capacity and good high-voltage cycle stability, has been widely adopted and holds a significant position among lithium-ion battery cathode materials.

[0003] Traditional lithium cobalt oxide cathode materials have a space group of R-3m and an oxygen packing sequence of ABCABC, belonging to the O3 phase structure. O3 phase lithium cobalt oxide cathode materials can achieve a capacity of 190 mAh / g at a charging cutoff voltage of 4.5V. However, with further increases in lithium battery voltage, the O3 phase lithium cobalt oxide undergoes a series of irreversible phase transitions, such as from the O3 phase to the H1-3 phase and from the H1-3 phase to the O1 phase, significantly reducing the electrochemical stability of the cathode material.

[0004] To improve the compaction density and electrochemical performance of cathode materials and meet the growing demand for high energy density in lithium batteries, P2-phase sodium cobalt oxide can be ion-exchanged to prepare O2-phase lithium cobalt oxide.

[0005] The O2 phase is a metastable structure that transforms into the O3 phase at temperatures exceeding 300°C. O2-phase lithium cobalt oxide is typically prepared through ion exchange in solution. However, current techniques generally require 1-2 days of ion exchange to produce high-purity O2-phase lithium cobalt oxide, and the resulting lithium cobalt oxide cathode material exhibits low compaction density and electrochemical performance. Summary of the Invention

[0006] This application provides a cathode material for lithium batteries and a method for preparing the same. The method includes two ion exchanges, which shortens the total ion exchange time, improves production efficiency, and results in a higher lithium content in the cathode material. It also increases the compaction density and specific capacity of the cathode material, which is beneficial for lithium batteries containing this cathode material to maintain good capacity retention at high voltages. This application also provides a lithium battery and an electrical device containing this cathode material.

[0007] In a first aspect, embodiments of this application provide a method for preparing a positive electrode material for lithium batteries. The preparation method includes two ion exchanges, wherein the two ion exchanges include: reacting Na... c (Co y M 1-yO2 and a first soluble lithium salt undergo a first ion exchange in a first solvent to obtain a first intermediate product. The duration T1 of the first ion exchange satisfies the relationship: 0.5h ≤ T1 ≤ 5h. The first intermediate product is then subjected to a second soluble lithium salt in a second solvent for a second ion exchange to obtain a second intermediate product. The duration T2 of the second ion exchange satisfies the relationship: 0.5h ≤ T2 ≤ 5h. A cathode material is then prepared from the second intermediate product. The chemical formula of the cathode material is Li. a Na b (Co x M 1-x O2; wherein, 0.5≤c≤0.9, 0<y≤1, 0.9≤a≤1, 0≤b≤0.1, 0<x≤1, and M is selected from at least one of Ca, Mg, Ni, Ba, Mn, Zr, Cr, Mo, Nb, Sb, Si, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Al, Fe and Sr.

[0008] The method in this application embodiment uses Na c (Co y M 1-y O2 is mixed with the first soluble lithium salt to obtain the first intermediate product. In the initial stage of the reaction, Na... c (Co y M 1-y In O2, the concentration of sodium ions is high and the concentration of lithium ions is low, resulting in a faster rate of the first ion exchange. As the reaction proceeds, the concentration of sodium ions increases. c (Co y M 1-y Sodium and lithium ions in O2 tend to reach equilibrium, and the ion exchange rate decreases. Then, a second soluble lithium salt is added to maintain a high ion concentration difference at the reaction interface, continuously enhancing and promoting the rapid second ion exchange, shortening the time to reach a new equilibrium. Through the two ion concentration differences in the two steps, the total time for the industrial-scale preparation of cathode materials is shortened, and production efficiency is improved.

[0009] Because the total time for the industrial-scale preparation of cathode materials is shortened, the material spends less time in the solvent, reducing the depolymerization and corrosion of the cathode material by the solution, improving the compaction density and morphological stability of the cathode material, which is beneficial for lithium batteries to have good capacity retention at high voltage.

[0010] The method in this application embodiment, through Na c (Co y M 1-y The mixing of O2 with the first soluble lithium salt and the mixing of the first intermediate with the second soluble lithium salt reset the concentrations of sodium and lithium in the reaction system, maintaining a high local concentration gradient in each step, accelerating the diffusion process, and maintaining a high driving force for ion exchange; breaking the Na...c (Co y M 1-y The "equilibrium" formed after mixing O2 with the first soluble lithium salt results in a more negative Gibbs free energy change (ΔG) when the second soluble lithium salt is added, which pushes the ion exchange reaction in the positive direction. The synergistic effect of the two equilibria in the above reaction system increases the ion exchange rate between lithium ions and sodium ions, resulting in a higher lithium content in the cathode material, thereby increasing the specific capacity of the cathode material.

[0011] In some optional embodiments, the duration T1 of the first ion exchange satisfies the relationship: 1h ≤ T1 ≤ 2h.

[0012] In some optional embodiments, the duration T2 of the second ion exchange satisfies the relationship: 1h ≤ T2 ≤ 2h.

[0013] In some alternative embodiments, the temperature of the first ion exchange is 60°C to 110°C.

[0014] In some alternative embodiments, the temperature of the second ion exchange is 60°C to 110°C.

[0015] In some optional embodiments, the molar ratio of Li to Na in the first ion exchange is (5-25):1.

[0016] In some optional embodiments, the molar ratio of Li to Na in the second ion exchange is (5-25):1.

[0017] In some alternative embodiments, the first ion exchange includes exchanging Na... c (Co y M 1-y O2 and a first soluble lithium salt are stirred and mixed in a first solvent at a stirring speed of 200 rpm to 1000 rpm to obtain a first intermediate product.

[0018] In some optional embodiments, the second ion exchange includes mixing the first intermediate product with a second soluble lithium salt in a second solvent by stirring at a speed of 200 rpm to 1000 rpm to obtain the second intermediate product.

[0019] In some optional embodiments, the cathode material prepared from the second intermediate product further includes a third ion exchange, a fourth ion exchange, and a fifth ion exchange.

[0020] In some optional embodiments, the preparation of the cathode material from the second intermediate product includes: performing a third ion exchange between the second intermediate product and a third soluble lithium salt in a third solvent to obtain the third intermediate product.

[0021] In some optional embodiments, the preparation of the third intermediate product further includes: performing a fourth ion exchange between the third intermediate product and a fourth soluble lithium salt in a fourth solvent.

[0022] In some optional embodiments, the first soluble lithium salt, the second soluble lithium salt, the third soluble lithium salt, and the fourth soluble lithium salt are each independently selected from one or more of lithium nitrate, lithium hydroxide, lithium carbonate, lithium chloride, lithium iodide, lithium fluoride, lithium bromide, and lithium phosphate.

[0023] In some optional embodiments, the concentration of the first soluble lithium salt in the first solvent is 1 to 5 mol / L;

[0024] In some optional embodiments, the concentration of the second soluble lithium salt in the second solvent is 1 to 5 mol / L.

[0025] In some optional embodiments, the concentration of the third soluble lithium salt in the third solvent is 1 to 5 mol / L;

[0026] In some optional embodiments, the concentration of the fourth soluble lithium salt in the fourth solvent is 1 to 5 mol / L.

[0027] In some optional embodiments, the first solvent, the second solvent, the third solvent, and the fourth solvent are each independently selected from water, organic solvents, or a mixture thereof.

[0028] In some alternative embodiments, Na c (Co y M 1-y The preparation method of O2 includes: mixing a sodium source and a transition metal source at a molar ratio of (0.5-0.9):1, heating to 500℃-1500℃ and calcining for 10-25 hours to obtain Na. c (Co y M 1-y O2, where 0.5≤c≤0.9, 0<y≤1.

[0029] In some optional embodiments, after the first ion exchange and / or after the second ion exchange, a post-treatment step is further included independently, which includes filtration, washing, drying and sieving, wherein the drying temperature is 80°C to 120°C.

[0030] Secondly, embodiments of this application provide a positive electrode material for lithium batteries, the positive electrode material having the chemical formula Li. a Na b (Co x M 1-xO2, wherein 0.9≤a≤1, 0≤b≤0.1, 0<x≤1, and M is selected from at least one of Ca, Mg, Ni, Ba, Mn, Zr, Cr, Mo, Nb, Sb, Si, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Al, Fe, and Sr; the compaction density of the cathode material after being compacted under 3 tons of pressure in a circular test sample with a radius of 6.5 mm is 4.10 g / cm³. 3 Up to 4.35 g / cm 3 .

[0031] In some optional embodiments, in the X-ray diffraction pattern of the cathode material, the ratio of A1 / (A1+A2) of the cathode material is greater than or equal to 0.95 and less than 1, where A1 represents the area of ​​the diffraction characteristic peak at a diffraction angle 2θ of 18° to 20°, and A2 represents the area of ​​the diffraction characteristic peak at a diffraction angle 2θ of 14° to 17°.

[0032] In some alternative embodiments, the specific capacity of the cathode material is from 185 mAh / g to 205 mAh / g at a voltage of 4.5 V and a current of 0.1 C.

[0033] In some alternative embodiments, the cathode material has a specific capacity of 210 mAh / g to 225 mAh / g at a voltage of 4.6 V and a current of 0.1 C.

[0034] Thirdly, embodiments of this application provide a lithium battery, which includes an electrode made of a positive electrode material obtained by the preparation method of the first aspect or a positive electrode material of the second aspect.

[0035] Fourthly, embodiments of this application provide an electrical device, including the lithium battery of the first aspect. Attached Figure Description

[0036] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments of this application will be briefly described below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0037] Figure 1 The X-ray diffraction pattern of the cathode material after 1 hour of the first ion exchange in Example 1 of this application is shown.

[0038] Figure 2 The X-ray diffraction pattern of the cathode material after 1 hour of second ion exchange in Example 1 of this application is shown.

[0039] Figure 3The X-ray diffraction pattern of the cathode material after 6 hours of first ion exchange in Comparative Example 2 of this application is shown. Detailed Implementation

[0040] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the positive electrode material for lithium batteries, methods for preparing the same, lithium batteries, and electrical devices of this application. However, unnecessary details may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0041] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60–120 and 80–110 are listed for specific parameters, it is understood that ranges of 60–110 and 80–120 are also expected. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1–3, 1–4, 1–5, 2–3, 2–4, and 2–5. In this application, unless otherwise stated, the numerical range "a–b" represents a shortened representation of any combination of real numbers between a and b, characterized in that a and b are both real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0042] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0043] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.

[0044] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0045] In this application, "multiple" refers to two or more (including two). "Multiple times" refers to two or more (including two).

[0046] Lithium batteries can be lithium-ion battery cells, lithium metal battery cells, lithium-sulfur battery cells, lithium solid-state batteries, etc., and can be primary lithium batteries or secondary lithium batteries. This application does not limit this.

[0047] Lithium-ion secondary batteries may include an outer packaging that encapsulates the electrode components and electrolyte. The outer packaging can be a rigid shell, such as a hard plastic shell, aluminum shell, or steel shell. It can also be a flexible package, such as a pouch. The material of the flexible package can be plastic, such as one or more of aluminum-plastic film, polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0048] The lithium battery provided in this application includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode, a negative electrode, and a separator. The electrode assembly can be a wound structure or a stacked structure, and this application does not limit this.

[0049] [Positive electrode plate]

[0050] In some alternative embodiments, the positive electrode may include a positive current collector and a positive electrode material layer disposed on at least one side of the positive current collector. The positive electrode material layer may be disposed on one or both surfaces of the positive current collector.

[0051] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode material is disposed on either or both of the two opposite surfaces of the positive current collector.

[0052] As an example, the positive current collector can be made of metal foil, conductive polymer material, carbon material, or composite current collector. For example, as a metal foil, it can be made of pure metal, alloy, or surface-treated metal, including but not limited to stainless steel, copper, aluminum, nickel, titanium, or silver.

[0053] In some optional embodiments, the positive electrode material layer includes a positive electrode binder and a positive electrode conductive agent. In some optional embodiments, the positive electrode material layer includes 0.1% to 5% positive electrode binder and 0.1% to 5% positive electrode conductive agent.

[0054] This application does not impose any particular limitation on the type of positive electrode conductive agent. As an example, the positive electrode conductive agent includes one or more of the following: superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0055] This application does not impose any particular limitation on the type of positive electrode binder. As an example, the positive electrode binder may include one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.

[0056] In some optional embodiments, the positive electrode includes a positive electrode material layer. In some optional embodiments, the positive electrode material layer includes a positive electrode material.

[0057] Preparation method of positive electrode material

[0058] This application provides a method for preparing a positive electrode material for lithium batteries. The preparation method includes two ion exchanges, each of which includes steps 100 to 200.

[0059] Step 100, Na c (Co y M 1-y O2 and the first soluble lithium salt undergo a first ion exchange in a first solvent to obtain a first intermediate product. The duration T1 of the first ion exchange satisfies the relationship: 0.5h≤T1≤5h, which can be selected as 1h≤T1≤2h.

[0060] Optionally, the duration T1 of the first ion exchange can be 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, or 2. Any value or a range thereof from 7h, 2.8h, 2.9h, 3.0h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h, 4.0h, 4.1h, 4.2h, 4.3h, 4.4h, 4.5h, 4.6h, 4.7h, 4.8h, 4.9h, and 5.0h.

[0061] It is understandable that the duration T1 of the first ion exchange can vary from Na to Na+. c (Co y M 1-y The calculation begins when O2 is mixed or comes into contact with the first soluble lithium salt. The time when the reaction product in the mixed system leaves the solvent is taken as the end time. For example, when the reaction product is filtered, the time when the reaction product leaves the first solvent is taken as the end time of duration T1.

[0062] If the reaction time (T1) of the first ion exchange is too long (T1 > 5 h), it will lead to Na+ ion exchange failure. c (Co y M 1-y The O2 structure is damaged, affecting the performance of the cathode material. The reaction time T1 of the first ion exchange is too short (T1 < 0.5 h), resulting in insufficient ion exchange, which affects the lithium content in the cathode material and also its performance.

[0063] In this step, Na c (Co y M 1-y When O2 and the first soluble lithium salt are mixed in the first solvent, in the initial stage of the reaction, Na... c (Co y M 1-y In O2, the concentration of sodium ions is high and the concentration of lithium ions is low, resulting in a significant concentration gradient between them. This leads to a rapid first ion exchange rate, with most sodium ions being replaced by lithium ions within a short time. Lithium ions then enter the Na+ ion exchange process within a relatively short time (T1). c (Co y M 1-y The transition metal layer in O2 is used to maintain the O2 / P2 structure, achieve the purpose of initially stabilizing the layered structure, and suppress the formation of oxygen vacancies in the crystal.

[0064] Step 200: The first intermediate product and the second soluble lithium salt are subjected to a second ion exchange in a second solvent to obtain the second intermediate product. The duration T2 of the second ion exchange satisfies the relationship: 0.5h≤T2≤5h, which can be selected as 1h≤T2≤2h.

[0065] Optionally, the duration T2 of the second ion exchange can be 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, or 2. Any value or a range thereof from 7h, 2.8h, 2.9h, 3.0h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h, 4.0h, 4.1h, 4.2h, 4.3h, 4.4h, 4.5h, 4.6h, 4.7h, 4.8h, 4.9h, and 5.0h.

[0066] The cathode material is prepared from the second intermediate product. The chemical formula of the cathode material is Li. a Na b (Co x M 1-x O2;

[0067] Wherein, 0.5≤c≤0.9, 0<y≤1, 0.9≤a≤1, 0≤b≤0.1, 0<x≤1, and M is selected from at least one of Ca, Mg, Ni, Ba, Mn, Zr, Cr, Mo, Nb, Sb, Si, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Al, Fe, and Sr.

[0068] Optionally, M is selected from at least one of Ca, Mg, Ni, Mn, La, Ti, Al, and Sr.

[0069] Optionally, c can be any value between 0.5, 0.6, 0.7, 0.8, 0.9, or 0.5 to 0.9; y can be any value between 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 0 to 1; a can be any value between 0.9, 0.95, 0.98, 0.99, 1, or 0.9-1; b can be any value between 0, 0.01, 0.05, 0.08, 0.09, 0.1, or 0 to 0.1; and x can be any value between 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 0 to 1.

[0070] It is understandable that the duration T2 of the second ion exchange can be calculated from the time when the first intermediate product is mixed or comes into contact with the second soluble lithium salt, and the time when the reaction product in the mixed system leaves the second solvent is taken as the end time. For example, when filtering the reaction product, the time when the reaction product leaves the second solvent is taken as the end time of duration T2.

[0071] If the reaction time (T2) of the second ion exchange is too long (T2 > 5 h), it will cause damage to the morphology and structure of the cathode material, affecting its performance. If the reaction time (T2) of the second ion exchange is too short (T2 < 0.5 h), the ion exchange will be insufficient, affecting the lithium content in the cathode material and also its performance.

[0072] Studies have found that during the ion exchange process of the cathode material, if the time for the first or second ion exchange is too short, especially when T2 < 0.5 h, excessive residual P2 phase results in a significant decrease in coin cell rate performance and poor cycle stability. Conversely, if the time for the first or second ion exchange is greater than 5 h, the morphology and structure of the cathode material are disrupted, affecting its compaction density.

[0073] In this step, when the first intermediate product and the second soluble lithium salt are mixed in the second solvent, the added second soluble lithium salt maintains a high ion concentration gradient at the reaction interface, continuously enhancing and rapidly promoting the second ion exchange, shortening the time to reach a new equilibrium, and achieving secondary ion exchange in a shorter time T2, thus freeing up the remaining small portion of Na+. c (Co y M 1-y Sodium ions were successfully displaced from the lithium sites of the alkali metal layer of O2, shortening the duration T2 of the second ion exchange. This reduced the total time of the two ion exchanges, decreasing the depolymerization and corrosion of the cathode material by the solution, improving the compaction density and morphological stability of the cathode material, and contributing to good capacity retention of the lithium battery at high voltages.

[0074] The method in this application embodiment uses Na c (Co y M 1-y O2 is mixed with the first soluble lithium salt to obtain the first intermediate product. In the initial stage of the reaction, Na... c (Co y M 1-y In O2, the concentration of sodium ions is high and the concentration of lithium ions is low, resulting in a faster rate of the first ion exchange. As the reaction proceeds, the concentration of sodium ions increases. c (Co y M 1-y Sodium and lithium ions in O2 tend to reach equilibrium, and the ion exchange rate decreases. Then, a second soluble lithium salt is added to maintain a high ion concentration difference at the reaction interface, continuously enhancing and promoting the rapid second ion exchange, shortening the time to reach a new equilibrium. Through the two ion concentration differences in the two steps, the total time for the industrial-scale preparation of cathode materials is shortened, and production efficiency is improved.

[0075] The method in this application embodiment, through Na c (Co y M1-y The mixing of O2 with the first soluble lithium salt and the mixing of the first intermediate with the second soluble lithium salt reset the concentrations of sodium and lithium in the reaction system, maintaining a high local concentration gradient in each step, accelerating the diffusion process, and maintaining a high driving force for ion exchange; breaking the Na... c (Co y M 1-y When O2 is mixed with the first soluble lithium salt, an "equilibrium" is formed. When the second soluble lithium salt is added, the Gibbs free energy change (ΔG) becomes more negative, which pushes the ion exchange reaction to the positive direction. The synergistic effect of the two equilibrations in the above reaction system increases the ion exchange rate between lithium ions and sodium ions, resulting in a higher lithium content in the cathode material, thereby increasing the specific capacity of the cathode material.

[0076] The ion exchange rate can be calculated as follows: Ion exchange rate = (molar amount of lithium ions in 1 mol of cathode material) / (sum of molar amounts of lithium ions and sodium ions in 1 mol of cathode material) × 100%

[0077] For example, using the preparation method of this application, the ion exchange rate can reach 98.1%-99.3%.

[0078] In some alternative embodiments, prior to step 100, Na c (Co y M 1-y The preparation method of O2 includes: mixing a sodium source and a transition metal source at a molar ratio of (0.5-0.9):1, heating to 500℃-1500℃ and calcining for 10-25 hours to obtain Na. c (Co y M 1-y O2, wherein the transition metal sources include cobalt and M sources, 0.5≤c≤0.9, 0<y≤1. Therefore, while considering economic efficiency and raw material utilization, high-purity P2-phase Na is obtained. c (Co y M 1-y )O2.

[0079] Optionally, the molar ratio of sodium source to transition metal source can be any of the following ratios or a range thereof: 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1. The endpoint temperature for heating can be any of the following values ​​or a range thereof: 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, 1300℃, 1350℃, 1400℃, 1450℃, 1500℃.

[0080] It is understandable that: Na c (Co y M 1-y O2 can be mainly in the P2 phase. c can be 0.5, 0.6, 0.7, 0.8, 0.9, etc.

[0081] Na c (Co y M 1-y The higher the sodium content in O2, the more sodium can be replaced per unit volume or mass of material. + The more sites there are, the more Li will be produced under the same reaction conditions. + It can participate in ion exchange, resulting in a higher final lithium content in the product cathode material. On the other hand, this indicates that the sodium cobaltate material has a more complete layered structure, which is conducive to Li... + The embedding within the material provides more ordered channels, which is beneficial for the thoroughness or completeness of ion exchange. In summary, Na c (Co y M 1-y The larger the carbon content (c) in O2, the better it is to increase the lithium content in the cathode material.

[0082] In some alternative embodiments, the sodium source includes one or more of sodium carbonate, sodium hydroxide, and sodium nitrate.

[0083] In some optional embodiments, the transition metal source includes a cobalt source and an M source. The cobalt source may include one or more of cobalt oxide, cobalt hydroxide, cobalt carbonate, cobalt nitrate, and cobalt acetate. The M source may include one or more of manganese, nickel, iron, aluminum, titanium, chromium, and copper.

[0084] For example, manganese sources include manganese oxide (MnO), manganese hydroxide (Mn(OH)2), manganese carbonate (MnCO3), manganese nitrate (Mn(NO3)2·4H2O), manganese sulfate (MnSO4·H2O), etc.; nickel sources include nickel oxide (NiO, Ni2O3), nickel hydroxide (Ni(OH)2), nickel carbonate (NiCO3), nickel nitrate (Ni(NO3)2·6H2O), nickel acetate (Ni(CH3COO)2·4H2O), etc.; iron sources include iron oxide (Fe2O3, Fe3O4, FeO), iron hydroxide (Fe(OH)3), ferrous carbonate (FeCO3), ferrous nitrate (Fe(NO3)3·9H2O), ferrous sulfate (FeSO4·7H2O), etc. The sources of aluminum include aluminum oxide (Al2O3), aluminum hydroxide (Al(OH)3), aluminum nitrate (Al(NO3)3·9H2O), aluminum sulfate (Al2(SO4)3·18H2O), aluminum isopropoxide (Al(OC3H7)3), etc.; the sources of titanium include titanium dioxide (TiO2), tetrabutyl titanate (Ti(OC4H9)4), titanium sulfate (Ti(SO4)2), titanium tetrachloride (TiCl4), etc.; the sources of chromium include chromium trioxide (Cr2O3), chromium hydroxide (Cr(OH)3), chromium nitrate (Cr(NO3)3·9H2O), chromium sulfate (Cr2(SO4)3), etc.; the sources of copper include copper oxide, cuprous oxide, copper hydroxide, copper nitrate, copper sulfate, etc.

[0085] In some optional embodiments, after calcination for 10 to 25 hours, Na... c (Co y M 1-y The preparation method of O2 also includes cooling the product to room temperature and then crushing and sieving it. The sieve used for sieving can be 200 mesh to 600 mesh.

[0086] In some optional embodiments, the first soluble lithium salt and the second soluble lithium salt respectively include one or more of lithium nitrate, lithium hydroxide, lithium carbonate, lithium chloride, lithium iodide, lithium fluoride, lithium bromide and lithium phosphate.

[0087] In some optional embodiments, the first soluble lithium salt comprises LiOH and / or LiCl. In some optional embodiments, the second soluble lithium salt comprises LiOH and / or LiCl. Using LiOH and / or LiCl as raw materials for both the first and second soluble lithium salts results in a cathode material free of impurity phase (T2 phase) formation, increases the proportion of the O2 phase, improves the overall stability of the cathode material, and enhances the cycle capacity retention rate in lithium batteries.

[0088] In some optional embodiments, the concentration of the first soluble lithium salt in the first solvent is 1–5 mol / L, and the concentration of the second soluble lithium salt in the second solvent is 1–5 mol / L. Optionally, the concentrations of the first soluble lithium salt in the first solvent and the second soluble lithium salt in the second solvent can be any value or a range thereof from 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, and 5 mol / L. This facilitates control of the concentration difference between lithium and sodium, enabling ion exchange, increasing the mass ratio of lithium in the cathode material, and thus improving the overall performance of the cathode material.

[0089] In some optional embodiments, the first solvent and the second solvent are independently selected from water, organic solvents, or mixtures thereof. Mixing the raw materials for preparing the cathode material in the first and second solvents facilitates sufficient contact between the raw materials, enabling ion exchange and improving reaction efficiency. The organic solvent can be ethanol, ethylene glycol, or other solvents.

[0090] In some optional embodiments, in step 100, during the first ion exchange, the temperature of the first ion exchange is between 60°C and 110°C. Optionally, the temperature of the first ion exchange can be any value or a range of combinations thereof from 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, and 110°C.

[0091] In some optional embodiments, in step 200, during the second ion exchange, the temperature of the second ion exchange is between 60°C and 110°C. Optionally, the temperature of the second ion exchange can be any value or a range of combinations thereof from 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, and 110°C.

[0092] Based on reaction thermodynamics, the lower the temperature of the first or second ion exchange, the slower the ion exchange rate; conversely, the higher the reaction temperature, the higher the ion exchange rate. To balance cost and production process safety, the aforementioned temperatures are beneficial for shortening the total preparation time and improving the production efficiency of cathode materials.

[0093] In some optional embodiments, in step 100, the molar ratio of Li to Na in the first ion exchange is (5-25):1.

[0094] Optionally, the molar ratio of Li to Na in the first ion exchange can be 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, 10:1, 10.5:1, 11:1, 11.5:1, 12:1, 12.5:1, 13:1, 13.5:1, 14:1, 14.5:1. Any ratio or a range thereof from 15:1, 15.5:1, 16:1, 16.5:1, 17:1, 17.5:1, 18:1, 18.5:1, 19:1, 19.5:1, 20:1, 20.5:1, 21:1, 21.5:1, 22:1, 22.5:1, 23:1, 23.5:1, 24:1, 24.5:1, 25:1.

[0095] A higher molar ratio of Li to Na indicates a higher initial ion concentration difference, which is beneficial for increasing the ion exchange rate, shortening the total preparation time, and improving production efficiency. However, an excessively high molar ratio of Li to Na will increase costs without significantly improving performance; a lithium-sodium molar ratio within the range of (5-25):1 is preferable.

[0096] In some optional embodiments, in step 200, the molar ratio of Li to Na in the second ion exchange is (5-25):1.

[0097] This demonstrates that resetting the ion concentration difference in the reaction system and increasing the ion concentration difference is beneficial for increasing the ion exchange rate, shortening the total preparation time, improving production efficiency, and taking into account economic benefits.

[0098] Optionally, the molar ratio of Li to Na in the second ion exchange can be 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, 10:1, 10.5:1, 11:1, 11.5:1, 12:1, 12.5:1, 13:1, 13.5:1, 14:1, 14.5:1. Any ratio or a range thereof from 15:1, 15.5:1, 16:1, 16.5:1, 17:1, 17.5:1, 18:1, 18.5:1, 19:1, 19.5:1, 20:1, 20.5:1, 21:1, 21.5:1, 22:1, 22.5:1, 23:1, 23.5:1, 24:1, 24.5:1, 25:1.

[0099] In some alternative embodiments, step 100, the first ion exchange, includes transferring Na... c (Co y M 1-yO2 and a first soluble lithium salt are stirred and mixed in a first solvent at a stirring speed of 200 rpm to 1000 rpm to obtain a first intermediate product. This facilitates thorough mixing of Na. c (Co y M 1-y O2 reacts with the first soluble lithium salt to achieve full exchange of lithium ions and sodium ions, shortening the total preparation time and improving production efficiency.

[0100] For example, stirring is performed at a stirring speed of any value or a range of combinations thereof, of 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, 850 rpm, 900 rpm, 950 rpm, and 1000 rpm.

[0101] In some optional embodiments, step 200, the second ion exchange, includes stirring and mixing the first intermediate product and the second soluble lithium salt in a second solvent at a stirring speed of 200 rpm to 1000 rpm to obtain the second intermediate product. This facilitates thorough mixing of the first intermediate product and the second soluble lithium salt, achieving sufficient exchange of lithium ions and sodium ions, shortening the total preparation time, and improving production efficiency.

[0102] For example, stirring is performed at a stirring speed of any value or a range of combinations thereof, of 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, 850 rpm, 900 rpm, 950 rpm, and 1000 rpm.

[0103] In some optional embodiments, after the first ion exchange and / or after the second ion exchange, a post-treatment step is further included independently. The post-treatment step includes filtration, washing, drying and sieving, wherein the drying temperature is 80°C to 120°C.

[0104] For example, the drying temperature can be any value or a range of combinations of 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, and 120°C.

[0105] In some alternative embodiments, the size of the sieve used for sieving is 200 mesh to 600 mesh.

[0106] In some optional embodiments, the preparation of the cathode material from the second intermediate product includes: performing a third ion exchange between the second intermediate product and a third soluble lithium salt in a third solvent to obtain a third intermediate product.

[0107] In some optional embodiments, the preparation of the third intermediate product further includes: performing a fourth ion exchange between the third intermediate product and a fourth soluble lithium salt in a fourth solvent.

[0108] It is understood that the preparation method of this application includes two ion exchanges, and may also include a third, fourth, or fifth ion exchange. That is, the preparation method of this application includes multiple ion exchanges, which can further improve the ion exchange rate, increase the lithium content in the cathode material, and thus improve the overall performance of the cathode material.

[0109] The reaction conditions for third, fourth, or fifth ion exchanges, such as temperature, reaction time, stirring speed, raw material molar ratio, and lithium salt type, can be referenced from those for first or second ion exchanges.

[0110] This application also provides a cathode material for lithium batteries, which can be prepared by the above-described preparation method.

[0111] cathode materials

[0112] In some optional embodiments, the positive electrode material has the chemical formula Li. a Na b (Co x M 1-x O2, wherein 0.9≤a≤1, 0≤b≤0.1, 0<x≤1, and M is selected from at least one of Ca, Mg, Ni, Ba, Mn, Zr, Cr, Mo, Nb, Sb, Si, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Al, Fe and Sr.

[0113] Optionally, M is selected from at least one of Ca, Mg, Ni, Mn, La, Ti, Al, and Sr.

[0114] Therefore, the cathode material is mainly composed of the O2 phase and has a high lithium content, which is beneficial to improving the overall performance of the cathode material and increasing the cycle capacity retention rate and mass energy density of the lithium battery.

[0115] In some optional embodiments, the compaction density of the cathode material, after being compacted under 3 tons of pressure in a circular test sample with a radius of 6.5 mm, is 4.0 g / cm³. 3 Up to 4.6 g / cm 3 .

[0116] In some optional embodiments, the compaction density of the cathode material, after being compacted under 3 tons of pressure in a circular test sample with a radius of 6.5 mm, is 4.10 g / cm³. 3 Up to 4.35 g / cm 3 The option is 4.15g / cm³. 3 Up to 4.35 g / cm 3 For example, the compaction density can be 4.11 g / cm³. 3 4.14 g / cm 3 4.16 g / cm 3 4.20g / cm 3 4.25g / cm 3 4.30 g / cm 3 4.34 g / cm 3 Any value in or a range thereof.

[0117] The compaction density of the cathode material is a well-known concept in the art and can be determined using methods known in the art. For example, it can be determined using an electronic pressure testing machine (e.g., UTM7305) in accordance with standard GB / T24533-2009.

[0118] In some optional embodiments, in the X-ray diffraction pattern of the cathode material, the ratio of A1 / (A1+A2) of the cathode material is greater than or equal to 0.95 and less than 1, where A1 represents the area of ​​the diffraction characteristic peak at a diffraction angle 2θ of 18° to 20°, and A2 represents the area of ​​the diffraction characteristic peak at a diffraction angle 2θ of 14° to 17°.

[0119] Optionally, the ratio of A1 / (A1+A2) of the cathode material can be any value or a range of combinations thereof from 0.950, 0.955, 0.960, 0.965, 0.970, 0.975, 0.980, 0.981, 0.982, 0.983, 0.984, 0.985, 0.986, 0.987, 0.988, 0.989, 0.990, 0.991, 0.992, 0.993, 0.994, 0.995, 0.996, 0.997, 0.998, and 0.999.

[0120] Research revealed that the diffraction characteristic peaks at 2θ angles of 18°–20° are the main characteristic peaks of the O2 phase, while those at 2θ angles of 14°–17° are the main characteristic peaks of the P2 phase. The proportion of the O2 phase can be represented by A1 / (A1+A2). O2 phase cathode materials exhibit excellent structural stability and electrochemical performance during long-term cycling, providing higher initial capacity. In the cathode material obtained through ion exchange using the preparation method described in this application, the area of ​​the diffraction characteristic peaks at 2θ angles of 18°–20° is relatively large, indicating a high proportion and purity of the O2 phase. This improves the structural stability of the cathode material, provides higher initial capacity, and enhances the cycle capacity retention rate of lithium batteries at high voltages.

[0121] In some optional embodiments, the specific capacity of the cathode material at 4.5V and 0.1C is from 185mAh / g to 205mAh / g, optionally from 188mAh / g to 201mAh / g. This is beneficial for improving the initial capacity and energy density of the lithium battery.

[0122] In some optional embodiments, the specific capacity of the cathode material at 4.6V and 0.1C is 210mAh / g to 225mAh / g, optionally 215mAh / g to 220mAh / g. This is beneficial for improving the initial capacity and energy density of the lithium battery.

[0123] [Negative electrode plate]

[0124] The specific composition and structure of the negative electrode sheet can be selected according to the type of lithium battery, and the embodiments of this application are not limited in this regard.

[0125] The negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector and comprising a negative active material. For example, the negative current collector has two surfaces opposite each other in its thickness direction, and the negative active material layer is disposed on either or both of the two opposite surfaces of the negative current collector.

[0126] The negative electrode active material is a material capable of extracting and inserting active ions, and can be any material known in the art. As examples, negative electrode active materials include, but are not limited to, one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. Silicon-based materials may include one or more of elemental silicon, silicon oxide, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide, and tin alloys. This application is not limited to these materials, and other conventionally known materials that can be used as negative electrode active materials may also be used.

[0127] [Isolation Component]

[0128] In some embodiments, the electrode assembly further includes a spacer disposed between the positive electrode and the negative electrode.

[0129] In some embodiments, the separator can be a separator membrane. This application does not impose any particular limitation on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.

[0130] As an example, the main material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride, and ceramic. The separator can be a single-layer film or a multi-layer composite film, without particular restrictions.

[0131] [Electrolytes]

[0132] In some alternative embodiments, the lithium battery includes an electrolyte. The electrolyte acts as a conductor of active ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte, which can be selected according to requirements. The electrolyte can be liquid, gel, or solid.

[0133] Liquid electrolytes include electrolyte salts and solvents.

[0134] In some alternative embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0135] In some alternative embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone. The solvent may also be an ether solvent. Ether solvents may include one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyl tetrahydrofuran, diphenyl ether, and crown ethers.

[0136] Electrical devices

[0137] This application provides an electrical device, including the lithium battery described above.

[0138] Lithium batteries can be used as a power source for electrical devices, or as an energy storage unit for electrical devices. The technical solutions described in the embodiments of this application are applicable to various electrical devices that use lithium batteries, such as mobile phones, portable devices, laptops, electric vehicles, electric toys, power tools, vehicles, ships, and spacecraft, etc. For example, spacecraft include airplanes, rockets, space shuttles, and spacecraft.

[0139] Example

[0140] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0141] Example 1

[0142] This application provides an embodiment of Li, a positive electrode material for lithium batteries. 0.99 Na 0.01 (Co 0.96 Mn 0.04 Methods for preparing O2 include:

[0143] P2 phase raw material Na c (Co y M 1-y Preparation of O2: Using analytical grade raw materials Na2CO3, Co3O4, and Mn2O3, weigh the corresponding weights of Na2CO3, Co3O4, and Mn2O3 according to their stoichiometric molar ratios. Then, add them to a mixer and mix at 2000 r / min for 3 min. Place the uniformly mixed material into a muffle furnace and maintain the temperature at 950℃ for 15 hours in air atmosphere. Then, cool with the furnace, crush using a universal pulverizer, and sieve through a 400-mesh sieve to obtain the molecular formula Na2CO3. 0.672 (Co 0.96 Mn 0.04 P2 phase raw material of O2.

[0144] Preparation of lithium salt solution: Dissolve lithium salts LiCl and LiOH in deionized water at a molar ratio of 1:1 to obtain a lithium salt solution with a lithium element concentration of 3 mol / L.

[0145] Ion exchange reaction process: The P2 phase raw material Na obtained above is reacted according to a Li / Na molar ratio of 15:1. 0.672 (Co 0.96 Mn0.04 O2 was added to a portion of the prepared lithium salt solution, and a first ion exchange was performed at 110°C for 1 hour (T1). The solution was then filtered, washed, and dried at 90°C to obtain Li. 0.955 Na 0.045 (Co 0.96 Mn 0.04 The first intermediate product of the first ion exchange of O2 is an O2-P2 mixed-phase material. During the first ion exchange, stirring is required at a speed of 800 rpm.

[0146] After the first ion exchange is completed, Li 0.955 Na 0.045 (Co 0.96 Mn 0.04 O2 is mixed with a portion of the lithium salt solution prepared above, wherein the amount of lithium salt solution added is based on the ratio of lithium element to Li in the lithium salt solution. 0.955 Na 0.045 (Co 0.96 Mn 0.04 The reaction proceeded with a Na molar ratio of 15:1 in O2, followed by a second ion exchange at 110℃ for 1 hour (T2). The reaction product was filtered, washed, dried at 90℃, and then sieved through a 400-mesh sieve to obtain a high-purity secondary ion exchange product of the final O2 phase, which is the cathode material Li. 0.990 Na 0.01 (Co 0.96 Mn 0.04 O2, wherein stirring is required during the second ion exchange, and the stirring speed is 800 rpm.

[0147] Example 2

[0148] The difference between this application and Example 1 is that the duration T1 of the first ion exchange is 2 hours; and the first intermediate product of the first ion exchange is Li. 0.963 Na 0.037 (Co 0.96 Mn 0.04 O2 was used to mix the first intermediate product with a lithium salt solution, followed by a second ion exchange, the duration of which was T2, which was 2 hours. The final product obtained was the cathode material Li. 0.993 Na 0.007 (Co 0.96 Mn 0.04 )O2.

[0149] Example 3

[0150] The difference between this application and Example 1 is that the duration T1 of the first ion exchange is 2 hours; and the first intermediate product of the first ion exchange is Li. 0.963 Na 0.037 (Co0.96 Mn 0.04 O2 was used to mix the first intermediate product with a lithium salt solution, followed by a second ion exchange, the duration of which was T2, 1 hour. The final product obtained was the cathode material Li. 0.992 Na 0.008 (Co 0.96 Mn 0.04 )O2.

[0151] Example 4

[0152] The difference between this application and Example 1 is that the duration T1 of the first ion exchange is 1 hour; and the first intermediate product of the first ion exchange is Li. 0.955 Na 0.045 (Co 0.96 Mn 0.04 O2 was used to mix the first intermediate product with a lithium salt solution for a second ion exchange, the duration of which was T2, 1 hour. The resulting second ion exchange product was Li. 0.990 Na 0.01 (Co 0.96 Mn 0.04 O2; After the second ion exchange is completed, the second ion exchange product Li is removed. 0.990 Na 0.01 (Co 0.96 Mn 0.04 O2 is mixed with a portion of the lithium salt solution prepared above, wherein the amount of lithium salt solution added is based on the ratio of lithium element to Li in the lithium salt solution. 0.990 Na 0.01 (Co 0.96 Mn 0.04 The reaction proceeds with a Na molar ratio of 15:1 in O2, undergoing a third ion exchange at 110℃ for 1 hour (T3). The reaction product is filtered, washed, dried at 90℃, and then sieved through a 400-mesh sieve to obtain a high-purity third ion exchange product of the final O2 phase, i.e., the final product, which is the cathode material Li. 0.993 Na 0.007 (Co 0.96 Mn 0.04 )O2.

[0153] Example 5

[0154] This application provides an embodiment of Li, a positive electrode material for lithium batteries. 0.987 Na 0.013 (Co 0.93 Ni 0.02 Mn 0.05 Methods for preparing O2 include:

[0155] P2 phase raw material Na c (Coy M 1-y Preparation of O2: Using analytical grade raw materials Na2CO3, Co3O4, NiO, and Mn2O3, weigh the corresponding weights of Na2CO3, Co3O4, NiO, and Mn2O3 according to their stoichiometric molar ratios. Then, add them to a mixer and mix at 2000 r / min for 3 min. Place the uniformly mixed material into a muffle furnace and maintain the temperature at 950℃ for 15 hours in air atmosphere. Then, cool with the furnace, crush using a universal pulverizer, and sieve through a 400-mesh sieve to obtain the molecular formula Na2CO3. 0.691 (Co 0.93 Ni 0.02 Mn 0.05 P2 phase raw material of O2.

[0156] Preparation of lithium salt solution: Dissolve lithium salts LiCl and LiOH in deionized water at a molar ratio of 1:1 to obtain a lithium salt solution with a lithium element concentration of 3 mol / L.

[0157] Ion exchange reaction process: The P2 phase raw material Na obtained above is reacted according to a Li / Na molar ratio of 12:1. 0.691 (Co 0.93 Ni 0.02 Mn 0.05 O2 was added to a portion of the prepared lithium salt solution, and a first ion exchange was performed at 100°C for 1 hour (T1). The solution was then filtered, washed, and dried at 90°C to obtain Li. 0.949 Na 0.051 (Co 0.93 Ni 0.02 Mn 0.05 The first intermediate product of the first ion exchange of O2 is an O2-P2 mixed-phase material. During the first ion exchange, stirring is required at a speed of 800 rpm.

[0158] After the first ion exchange is completed, Li 0.949 Na 0.051 (Co 0.93 Ni 0.02 Mn 0.05 O2 is mixed with a portion of the prepared lithium salt solution, wherein the amount of lithium salt solution added is based on the ratio of lithium element in the lithium salt solution to that in the raw material Li. 0.949 Na 0.051 (Co 0.93 Ni 0.02 Mn 0.05 The reaction proceeded with a Na molar ratio of 12:1 in O2, followed by a second ion exchange at 100℃ for 1 hour (T2). The reaction product was filtered, washed, dried at 90℃, and then sieved through a 400-mesh sieve to obtain a high-purity secondary ion exchange product of the final O2 phase, which is the cathode material Li.0.987 Na 0.013 (Co 0.93 Ni 0.02 Mn 0.05 O2, wherein stirring is required during the second ion exchange, and the stirring speed is 800 rpm.

[0159] Example 6

[0160] This application provides an embodiment of Li, a positive electrode material for lithium batteries. 0.983 Na 0.017 (Co 0.973 Al 0.027 Methods for preparing O2 include:

[0161] P2 phase raw material Na c (Co y M 1-y Preparation of O2: Using analytical grade raw materials, weigh out the corresponding weights of Na2CO3, Co3O4, and Al2O3 according to the stoichiometric molar ratio of their chemical formulas. Add these to a mixer and mix at 2000 r / min for 3 min. Place the uniformly mixed material into a muffle furnace and maintain the temperature at 950℃ for 15 hours in air atmosphere. Then cool with the furnace. After crushing in a universal pulverizer and sieving through a 400-mesh sieve, obtain the molecular formula Na2CO3. 0.708 (Co 0.973 Al 0.027 P2 phase raw material of O2.

[0162] Preparation of lithium salt solution: Dissolve lithium salts LiCl and LiOH in deionized water at a molar ratio of 1:1 to obtain a lithium salt solution with a lithium element concentration of 3 mol / L.

[0163] Ion exchange reaction process: The P2 phase raw material Na is then added according to a Li / Na molar ratio of 10:1. 0.708 (Co 0.973 Al 0.027 O2 was added to a lithium salt solution, and a first ion exchange was performed at 100°C for 1 hour (T1). The solution was then filtered, washed, and dried at 90°C to obtain Li. 0.951 Na 0.049 (Co 0.973 Al 0.027 The first intermediate product of the first ion exchange of O2. During the first ion exchange, stirring is required at a speed of 800 rpm.

[0164] After the first ion exchange is completed, Li 0.951 Na 0.049 (Co 0.973 Al 0.027O2 was mixed with the prepared lithium salt solution and subjected to a second ion exchange at 100°C with a Li / Na molar ratio of 10:1 for 1 hour (T2). The final product was filtered, washed, dried at 90°C, and sieved through a 400-mesh sieve to obtain a secondary ion exchange product with high purity of the final O2 phase. The cathode material is Li. 0.983 Na 0.017 (Co 0.973 Al 0.027 O2, wherein stirring is required during the second ion exchange, and the stirring speed is 800 rpm.

[0165] Example 7

[0166] This application provides an embodiment of Li, a positive electrode material for lithium batteries. 0.984 Na 0.016 (Co 0.97 Ti 0.03 Methods for preparing O2 include:

[0167] P2 phase raw material Na c (Co y M 1-y Preparation of O2: Using analytical grade raw materials, weigh out the corresponding weights of Na2CO3, Co3O4, and TiO2 according to the stoichiometric molar ratio of their chemical formulas. Then add them to a mixer and mix at 2000 r / min for 3 min. Place the uniformly mixed material into a muffle furnace and maintain the temperature at 950℃ for 15 hours in air atmosphere. Then cool with the furnace, crush the mixture using a universal pulverizer, and sieve it through a 400-mesh sieve to obtain the molecular formula Na2CO3. 0.679 (Co 0.97 Ti 0.03 P2 phase raw material of O2.

[0168] Preparation of lithium salt solution: Dissolve lithium salts LiCl and LiOH in deionized water at a molar ratio of 2:1 to obtain a lithium salt solution with a lithium element concentration of 3 mol / L.

[0169] Ion exchange reaction process: The P2 phase raw material Na is reacted according to a Li / Na molar ratio of 10:1. 0.679 (Co 0.97 Ti 0.03 O2 was added to a lithium salt solution, and a first ion exchange was performed at 100°C for 1 hour. After filtration, washing, and drying at 90°C, the resulting product had the molecular formula Li. 0.957 Na 0.043 (Co 0.97 Ti 0.03 The first intermediate product of the first ion exchange of O2 is an O2-P2 mixed-phase material. During the first ion exchange, stirring is required at a speed of 800 rpm.

[0170] After the first ion exchange was completed, Li was removed. 0.957 Na 0.043 (Co 0.97 Ti 0.03 O2 and the prepared lithium salt solution were mixed, and a second ion exchange was carried out at 100°C for 1 hour at a Li / Na molar ratio of 10:1. The final product was filtered, washed, dried at 90°C, and then sieved through a 400-mesh sieve to obtain a secondary ion exchange product with high purity of O2 phase. 0.984 Na 0.016 (Co 0.97 Ti 0.03 The O2 cathode material requires stirring during the second ion exchange at a speed of 800 rpm.

[0171] Example 8

[0172] This application provides an embodiment of Li, a positive electrode material for lithium batteries. 0.981 Na 0.019 (Co 0.97 Mg 0.03 Methods for preparing O2 include:

[0173] P2 phase raw material Na c (Co y M 1-y Preparation of O2: Using analytical grade raw materials, weigh out the corresponding weights of Na2CO3, Co3O4, and MgO according to the stoichiometric molar ratio of their chemical formulas. Then add them to a mixer and mix at 2000 r / min for 3 min. Place the uniformly mixed material into a muffle furnace and maintain the temperature at 950℃ for 15 hours in air atmosphere. Then cool with the furnace, crush the mixture using a universal pulverizer, and sieve it through a 400-mesh sieve to obtain the molecular formula Na2CO3. 0.739 (Co 0.97 Mg 0.03 P2 phase raw material of O2.

[0174] Preparation of lithium salt solution: Dissolve lithium salts LiCl and LiOH in deionized water at a molar ratio of 2:1 to obtain a lithium salt solution with a lithium element concentration of 3 mol / L.

[0175] Ion exchange reaction process: The P2 phase raw material Na is reacted according to a Li / Na molar ratio of 10:1. 0.739 (Co 0.97 Mg 0.03 O2 was added to a lithium salt solution, and a first ion exchange was performed at 100°C for 1 hour. After filtration, washing, and drying at 90°C, the resulting product had the molecular formula Li. 0.954 Na 0.046 (Co 0.97 Mg 0.03The first intermediate product of the first ion exchange of O2 is the O2-P2 mixed-phase material. During the first ion exchange, stirring is required at a speed of 800 rpm.

[0176] After the first ion exchange is completed, Li 0.954 Na 0.046 (Co 0.97 Mg 0.03 O2 and the prepared lithium salt solution were added to the lithium salt-containing solution at a Li / Na molar ratio of 10:1. A second ion exchange was performed at 100°C for 1 hour. The final product was filtered, washed, dried at 90°C, and then sieved through a 400-mesh sieve to obtain a secondary ion exchange product with high purity of the final O2 phase. 0.981 Na 0.019 (Co 0.97 Mg 0.03 The O2 cathode material requires stirring during the second ion exchange at a speed of 800 rpm.

[0177] Comparative Example 1

[0178] This application provides a comparative example of a positive electrode material Li for lithium batteries. 0.953 Na 0.047 Methods for preparing CoO2 include:

[0179] P2 phase raw material Na c (Co y M 1-y Preparation of O2: Using analytical grade raw materials, weigh out the corresponding weights of Na2CO3 and Co3O4 according to the stoichiometric molar ratio of their chemical formulas. Add them to a mixer and mix at 2000 r / min for 3 min. Place the uniformly mixed material into a muffle furnace and maintain the temperature at 950℃ for 15 hours in air atmosphere. Then cool with the furnace, crush the mixture using a universal pulverizer, and sieve it through a 400-mesh sieve to obtain the molecular formula Na2CO3. 0.7 P2 phase raw material of CoO2.

[0180] Preparation of lithium salt solution: Dissolve lithium salts LiCl and LiOH in deionized water at a molar ratio of 1:1 to obtain a lithium salt solution with a lithium element concentration of 3 mol / L.

[0181] Ion exchange reaction process: The P2 phase raw material Na is reacted according to a Li / Na molar ratio of 10:1. 0.7 CoO2 was added to a lithium salt solution, and a first ion exchange was performed at 100°C for 24 hours. After filtration, washing, and drying at 90°C, Li was obtained. 0.953 Na 0.047 The positive electrode material is CoO2. During the first ion exchange, stirring is required at a speed of 800 rpm.

[0182] Comparative Example 2

[0183] This application provides a comparative example of a positive electrode material Li for lithium batteries. 0.972 Na 0.028 (Co 0.96 Mn 0.04 Methods for preparing O2 include:

[0184] P2 phase raw material Na c (Co y M 1-y Preparation of O2: Using analytical grade raw materials, weigh out the corresponding weights of Na2CO3, Co3O4, and Mn2O3 according to the stoichiometric molar ratio of their chemical formulas. Add these to a mixer and mix at 2000 r / min for 3 min. Place the uniformly mixed material into a muffle furnace and maintain the temperature at 950℃ for 15 hours in air atmosphere. Then cool with the furnace, crush the mixture using a universal pulverizer, and sieve it through a 400-mesh sieve to obtain the molecular formula Na2CO3. 0.672 (Co 0.96 Mn 0.04 P2 phase raw material of O2.

[0185] Preparation of lithium salt solution: Dissolve lithium salts LiCl and LiOH in deionized water at a molar ratio of 1:1 to obtain a lithium salt solution with a lithium element concentration of 3 mol / L.

[0186] Ion exchange reaction process: The P2 phase raw material Na is reacted according to a Li / Na molar ratio of 15:1. 0.672 (Co 0.96 Mn 0.04 O2 was added to a lithium salt solution, and a first ion exchange was performed at 110°C for 6 hours. After filtration, washing, and drying at 90°C, the resulting product had the molecular formula Li. 0.972 Na 0.028 (Co 0.96 Mn 0.04 The positive electrode material is O2. During the first ion exchange, stirring is required at a speed of 800 rpm.

[0187] Comparative Example 3

[0188] This application provides a comparative example of a positive electrode material Li for lithium batteries. 0.992 Na 0.008 (Co 0.96 Mn 0.04 Methods for preparing O2 include:

[0189] P2 phase raw material Na c (Co y M 1-yPreparation of O2: Using analytical grade raw materials, weigh out the corresponding weights of Na2CO3, Co3O4, and Mn2O3 according to the stoichiometric molar ratio of their chemical formulas. Add these to a mixer and mix at 2000 r / min for 3 min. Place the uniformly mixed material into a muffle furnace and maintain the temperature at 950℃ for 15 hours in air atmosphere. Then cool with the furnace, crush the mixture using a universal pulverizer, and sieve it through a 400-mesh sieve to obtain the molecular formula Na2CO3. 0.672 (Co 0.96 Mn 0.04 P2 phase raw material of O2.

[0190] Preparation of lithium salt solution: Dissolve lithium salts LiCl and LiOH in deionized water at a molar ratio of 1:1 to obtain a lithium salt solution with a lithium element concentration of 3 mol / L.

[0191] Ion exchange reaction process: The P2 phase raw material Na obtained above is reacted according to a Li / Na molar ratio of 12:1. 0.672 (Co 0.96 Mn 0.04 O2 was added to a portion of the prepared lithium salt solution, and a first ion exchange was performed at 100°C for 1 hour (T1). The solution was then filtered, washed, and dried at 90°C to obtain Li. 0.955 Na 0.045 (Co 0.96 Mn 0.04 The first intermediate product of the first ion exchange of O2 is an O2-P2 mixed-phase material. During the first ion exchange, stirring is required at a speed of 800 rpm.

[0192] After the first ion exchange is completed, Li 0.955 Na 0.045 (Co 0.96 Mn 0.04 O2 is mixed with a portion of the prepared lithium salt solution, wherein the amount of lithium salt solution added is based on the ratio of lithium element in the lithium salt solution to that in the raw material Li. 0.955 Na 0.045 (Co 0.96 Mn 0.04 The reaction proceeded with a Na molar ratio of 12:1 in O2, followed by a second ion exchange at 100℃ for 6 hours (T2). The reaction product was filtered, washed, dried at 90℃, and then sieved through a 400-mesh sieve to obtain a high-purity secondary ion exchange product of the final O2 phase, which is the cathode material Li. 0.992 Na 0.008 (Co 0.96 Mn 0.04 O2, wherein stirring is required during the second ion exchange, and the stirring speed is 800 rpm.

[0193] Test section

[0194] The positive electrode materials prepared in the examples and comparative examples, as well as the coin cells containing the positive electrode materials, were subjected to electrochemical performance tests.

[0195] (1) X-ray diffraction test: The cathode material was tested by X-ray diffraction technology according to the national standard GB / T 40407-2021 to obtain the X-ray diffraction pattern. The scanning range was 5°-80°, the scanning speed was 8° / min, the step angle was 0.02°, and the Sola slit was 5°.

[0196] (2) Cathode Material Compaction Density Test: The compaction density of the above-mentioned cathode material was tested using a Sansi Zongheng UIM7305 compaction density meter. The specific test procedure is as follows: 1g of cathode material was weighed on a balance and placed in a clean mold. The bottom area of ​​the mold was circular, and the radius of the hole inside the mold was 6.5mm. Then, the mold was placed on the pressure plate of the equipment, and the test pressure was selected as 2T and 3T respectively. The pressure was increased to 2000kg or 3000kg, held for 30s, then depressurized and held for 10s. The compaction density of the cathode material was then recorded and calculated.

[0197] (3) Ion exchange rate test: The content of metal elements in the above cathode material was tested using a PerkinElmer Optima 8300 ICP, and the ratio of lithium content to sodium and lithium content in the cathode material was calculated to obtain the ion exchange rate.

[0198] The ion exchange rate can be calculated as follows: Ion exchange rate = (molar amount of lithium ions in 1 mol of cathode material) / (sum of molar amounts of lithium ions and sodium ions in 1 mol of cathode material) × 100%

[0199] Assembly of the coin cell battery: The positive electrode material prepared in the above-described examples or comparative examples is mixed with a conductive agent (carbon black material) and a binder, polyvinylidene fluoride, in a mass ratio of 8:1:1. This mixture is then placed in the solvent N-methylpyrrolidone to form a slurry, which is then coated onto a 16μm aluminum foil. The slurry is then baked, rolled, and sliced ​​to form a positive electrode sheet with a total thickness of 44μm. Finally, the positive electrode sheet is assembled with a separator, lithium foil, and spacers to form a lithium-ion coin cell battery. The separator is a glass fiber membrane from Whatman Corporation.

[0200] The test conditions were as follows: at 25℃±2℃, the button cells prepared with the above cathode material were charged and discharged at 0.1C and 1C (nominal specific capacity 208mAh / g) in a voltage range of 3.0V-4.5V using the Blue Electric test system; or charged and discharged at 0.1C and 1C (nominal specific capacity 208mAh / g) in a voltage range of 3.0V-4.6V.

[0201] (4) Detection of the specific capacity of the positive electrode material: Perform charge and discharge at 4.5V and 0.1C rate, and record the discharge capacity. Or perform charge and discharge at 4.6V and 0.1C rate, and record the discharge capacity.

[0202] (5) Testing of the cycle capacity retention rate of button cells:

[0203] Charge the battery at a constant current of 1C to 4.5V, then charge it at a constant voltage of 4.5V to 0.05C. Let it rest for 5 minutes, then discharge it at 1C to 3.0V. This constitutes one charge-discharge cycle. Record the initial cycle discharge capacity C0 of the lithium-ion battery. Repeat this cycle 100 times. Record the cycle discharge capacity C1 of the 100th cycle. The 100-cycle capacity retention rate = C1 / C0 × 100%.

[0204] Charge the battery at a constant current of 1C to 4.6V, then charge it at a constant voltage of 4.6V to 0.05C. Let it rest for 5 minutes, then discharge it at 1C to 3.0V. This completes one charge-discharge cycle. Record the initial cycle discharge capacity C2 of the lithium-ion battery. Repeat this cycle 100 times. Record the cycle discharge capacity C3 of the 100th cycle. The 100-cycle capacity retention rate = C3 / C2 × 100%.

[0205] (6) Testing the rate performance of button cells:

[0206] Charge the battery to 4.5V at a constant current of 0.1C, then charge it to 0.05C at a constant voltage of 4.5V. Let it rest for 5 minutes, then discharge it to 3.0V at 0.1C. This constitutes one charge-discharge cycle. Perform 5 cycles and record the first cycle discharge capacity C4 of the lithium-ion battery. Then, repeat the above cycle process at 1C for 5 cycles. Record the first cycle discharge capacity C5 at 1C. 4.5V rate performance: 1C / 0.1C (%) = C5 / C4 × 100%.

[0207] Charge the battery at a constant current of 0.1C to 4.6V, then charge it at a constant voltage of 4.6V to 0.05C. Let it rest for 5 minutes, then discharge it at 0.1C to 3.0V. This constitutes one charge-discharge cycle. Perform 5 cycles and record the first cycle discharge capacity C6 of the lithium-ion battery. Then, repeat the above cycle process at 1C for 5 cycles. Record the first cycle discharge capacity C7 at 1C. 4.6V rate performance: 1C / 0.1C (%) = C7 / C6 × 100%.

[0208] The test results of Examples 1-8 and Comparative Examples 1-3 are shown in Table 1.

[0209]

[0210]

[0211] As shown in Table 1, compared to Comparative Examples 1-3, Examples 1-8, which employed multiple ion exchanges, resulted in a higher lithium content in the cathode material. This preparation method also achieved a higher ion exchange rate and shorter preparation time, thus improving production efficiency and reducing production costs. The cathode material prepared by the method described in this application exhibits high compaction density and specific capacity, and demonstrates good capacity retention under high voltage.

[0212] Examples 2-3 increased the ion exchange time by two times to varying degrees based on Example 1, while Example 4 designed a three-time ion exchange experiment. However, the improvement in ion exchange rate and electrochemical performance based on Example 1 was limited, and the compaction density decreased significantly after increasing the exchange time and number of exchanges.

[0213] The experimental results obtained from Examples 5-8 show that sodium cobaltate doped with Ni, Al, Ti or Mg has a high ion exchange rate and compaction density during the two ion exchange processes, which greatly improves the electrochemical performance of the cathode material in lithium batteries.

[0214] Comparative Example 1 uses raw material Na 0.7 The cathode materials prepared by CoO2 undergoing a long-term ion exchange have low compaction density and poor electrochemical performance. The ion exchange rate of this preparation method is poor. The reason for this is that the residual amount of P2 phase sodium cobaltate affects the performance of the cathode material.

[0215] Compared to Example 1, Comparative Example 2 only underwent a single ion exchange reaction lasting 6 hours, resulting in a minimal increase in ion exchange rate and a significant decrease in compaction density. Comparative Example 3 extended the reaction time for the second ion exchange, significantly reducing the compaction density, high-voltage cycle stability, and rate performance of the cathode material.

[0216] None of the comparative examples mentioned above used the preparation method of this application that includes two ion exchanges, i.e., no two soluble lithium salts were added, and only one ion exchange was performed. Moreover, the ion exchange time of the comparative examples was longer than the total ion exchange time of the embodiments of this application.

[0217] To ensure a high ion exchange rate (>98%) or a high mass percentage of lithium in the cathode material, the above comparative example can only extend the ion exchange reaction time. However, due to prolonged immersion in a high-temperature solvent, i.e., a lithium salt solution, the aggregated cathode material grains deagglomerate, and even the increased porosity leads to volume expansion, ultimately resulting in a cathode material with a compaction density not exceeding 3.900 g cm⁻¹. ﹣3 (3t). Moreover, the long-term high-temperature ion exchange reaction not only damages the material structure, but also increases production time and production costs, which is not conducive to the further industrialization of cathode materials.

[0218] The first intermediate product obtained from the first ion exchange in Examples 1-8 is obtained through a short-time ion exchange. This first intermediate product achieves an ion exchange rate of over 95%. However, due to the relatively high residual P2 phase, the electrochemical rate performance and cycle stability of the cathode material are still poor. Therefore, by resetting the lithium-sodium concentration gradient in the reaction system and performing a shorter-time second ion exchange, a higher ion exchange rate is achieved while ensuring that the compaction density of the cathode material or O2 phase lithium cobalt oxide does not decrease significantly during the second ion exchange. Ultimately, the resulting cathode material has a high ion exchange rate and minimal structural damage, resulting in superior overall electrochemical performance in lithium batteries.

[0219] Figure 1 The X-ray diffraction pattern of the cathode material after 1 hour of the first ion exchange in Embodiment 1 of this application is shown. It can be seen from the figure that the cathode material after 1 hour of the first ion exchange reacts with LiCoO2 and Na, respectively. 0.74 The position of the diffraction angle corresponding to CoO2 in Na 0.74 The diffraction peak area corresponding to the CoO2 position is smaller, while the diffraction peak area corresponding to the LiCoO2 position is larger, indicating that the Li element content in the cathode material is higher after 1 hour of the first ion exchange.

[0220] Figure 2 The X-ray diffraction pattern of the cathode material after the second ion exchange for 1 hour in Embodiment 1 of this application is shown; it can be seen from the figure that the cathode material after the first ion exchange for 1 hour reacts with LiCoO2 and Na, respectively. 0.74 The position of the diffraction angle corresponding to CoO2 in Na 0.74The diffraction peak area corresponding to the CoO2 position is almost non-existent, while the diffraction peak area corresponding to the LiCoO2 position is relatively large. This indicates that the cathode material after the first ion exchange for 1 hour has a high Li element content and almost no Na element.

[0221] Figure 3 The X-ray diffraction pattern of the cathode material after 6 hours of the first ion exchange in Comparative Example 2 of this application is shown. It can be seen from the figure that the cathode material after 6 hours of the first ion exchange reacts with LiCoO2 and Na, respectively. 0.74 The position of the diffraction angle corresponding to CoO2 in Na 0.74 The diffraction peak area corresponding to the CoO2 position is smaller, while the diffraction peak area corresponding to the LiCoO2 position is larger, indicating that the Li element in the cathode material after the first ion exchange for 6 hours is relatively smaller. Figure 2 The lithium content is relatively low.

[0222] In summary, this application employs a two-stage addition of soluble lithium salts, comprising a first soluble lithium salt and a second soluble lithium salt, to achieve two ion exchanges. This shortens the total ion exchange time for preparing the cathode material. This preparation method exhibits high ion exchange efficiency and produces cathode materials with both high compaction density and high specific capacity, as well as good stability. The first ion exchange allows most lithium ions to enter the transition metal layer of the P2 phase raw material to maintain the O2 / P2 structure, stabilize the layered structure, and suppress the formation of oxygen vacancies in high-voltage crystals. Further addition of the second soluble lithium salt, through a short second ion exchange, increases the concentration gradient between lithium and sodium ions, successfully displacing the remaining small portion of sodium ions, ultimately forming a structurally stable O2 phase cathode material. The method of this application can reduce the depolymerization and corrosion of the cathode material by the solution while ensuring a high ion exchange efficiency, improving the compaction density and morphological stability of the cathode material, thereby enhancing the electrochemical stability of the cathode material under high voltage in lithium batteries.

[0223] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A method for preparing a positive electrode material for lithium batteries, characterized in that, The preparation method includes two ion exchanges, the two ion exchanges comprising: Will Na c (Co y M 1-y O2 and a first soluble lithium salt undergo a first ion exchange in a first solvent to obtain a first intermediate product. The duration T1 of the first ion exchange satisfies the relationship: 0.5h≤T1≤5h. The first intermediate product is subjected to a second ion exchange with a second soluble lithium salt in a second solvent to obtain a second intermediate product. The duration T2 of the second ion exchange satisfies the relationship: 0.5h≤T2≤5h. The cathode material is prepared from the second intermediate product, and the chemical formula of the cathode material is Li. a Na b (Co x M 1-x O2; Wherein, 0.5≤c≤0.9, 0<y≤1, 0.9≤a≤1, 0≤b≤0.1, 0<x≤1, and M is selected from at least one of Ca, Mg, Ni, Ba, Mn, Zr, Cr, Mo, Nb, Sb, Si, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Al, Fe, and Sr.

2. The preparation method according to claim 1, characterized in that, The preparation method satisfies one or more of the following conditions: (1) The duration T1 of the first ion exchange satisfies the following relationship: 1h≤T1≤2h; (2) The duration T2 of the second ion exchange satisfies the following relationship: 1h≤T2≤2h; (3) The temperature of the first ion exchange is 60°C to 110°C; (4) The temperature of the second ion exchange is 60°C to 110°C; (5) The molar ratio of Li to Na in the first ion exchange is (5-25):1; (6) The molar ratio of Li to Na in the second ion exchange is (5-25):

1.

3. The preparation method according to claim 1 or 2, characterized in that, The first ion exchange includes the exchange of Na c (Co y M 1-y O2 and a first soluble lithium salt are stirred and mixed in a first solvent at a stirring speed of 200 rpm to 1000 rpm to obtain a first intermediate product; and / or, The second ion exchange involves mixing the first intermediate product with a second soluble lithium salt in a second solvent at a stirring speed of 200 rpm to 1000 rpm to obtain the second intermediate product.

4. The preparation method according to claim 1 or 2, characterized in that, The preparation method satisfies one or more of the following conditions: (1) The first soluble lithium salt and the second soluble lithium salt are each independently selected from one or more of lithium nitrate, lithium hydroxide, lithium carbonate, lithium chloride, lithium iodide, lithium fluoride, lithium bromide and lithium phosphate; (2) The concentration of the first soluble lithium salt in the first solvent is 1 to 5 mol / L; (3) The concentration of the second soluble lithium salt in the second solvent is 1 to 5 mol / L; (4) The first solvent and the second solvent are each independently selected from water and organic solvents or a mixture thereof.

5. The preparation method according to claim 1 or 2, characterized in that, The Na c (Co y M 1-y The preparation method of O2 includes: mixing a sodium source and a transition metal source at a molar ratio of (0.5-0.9):1, heating to 500℃-1500℃ and calcining for 10-25 hours to obtain Na. c (Co y M 1-y O2, where 0.5≤c≤0.9, 0<y≤1.

6. The preparation method according to claim 1 or 2, characterized in that, After the first ion exchange and / or the second ion exchange, a post-treatment step is independently included, which includes filtration, washing, drying and sieving, wherein the drying temperature is 80℃~120℃.

7. The preparation method according to claim 1 or 2, characterized in that, The process of obtaining the cathode material from the second intermediate product includes: ion exchange between the second intermediate product and a third soluble lithium salt in a third solvent.

8. A positive electrode material for lithium batteries, characterized in that, The chemical formula of the positive electrode material is Li a Na b (Co x M 1-x O2, wherein 0.9≤a≤1, 0≤b≤0.1, 0<x≤1, and M is selected from at least one of Ca, Mg, Ni, Ba, Mn, Zr, Cr, Mo, Nb, Sb, Si, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Al, Fe, and Sr; the cathode material, in a circular test sample with a radius of 6.5 mm, has a compaction density of 4.10 g / cm³ after being compacted under 3 tons of pressure. 3 Up to 4.35 g / cm 3 .

9. The positive electrode material according to claim 8, characterized in that, The cathode material satisfies one or more of the following conditions: (1) In the X-ray diffraction pattern of the cathode material, the ratio of A1 / (A1+A2) is greater than or equal to 0.95 and less than 1, where A1 represents the area of ​​the diffraction characteristic peak at a diffraction angle of 2θ of 18° to 20° and A2 represents the area of ​​the diffraction characteristic peak at a diffraction angle of 2θ of 14° to 17°. (2) The specific capacity of the positive electrode material at 4.5V voltage and 0.1C current is 185mAh / g to 205mAh / g; (3) The specific capacity of the cathode material at 4.6V voltage and 0.1C current is 210mAh / g to 225mAh / g.

10. A lithium battery, characterized in that, The lithium battery includes an electrode made of a positive electrode material prepared by any one of claims 1 to 7 or a positive electrode material prepared by claim 8 or 9.

11. An electrical device, characterized in that, Including the lithium battery of claim 10.